2022
DOI: 10.1007/s00011-022-01567-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-coronavirus vaccines will not accelerate the transition of humanity to a non-pandemic period, but the pandemic will take fewer victims

Abstract: The vaccination rate worldwide has reached enormous proportions, and it is likely that at least 75% of the world's population will be vaccinated. The controversy is that, while people aged 65 and older suffer a significantly higher mortality rate from COVID-19, plans are being made to vaccinate young people under the age of 20. Equally thorny is the question of vaccinating people who already have antibodies to SARS-CoV-2, as well as B and T memory cells, because they contracted and survived the virus. The poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…The emergence of the human coronavirus strain SARS‐CoV‐2 has thrown the world into the midst of a new pandemic, which remains an ongoing threat to human health. 29 Despite the fact that the majority of patients with SARS‐CoV‐2 infections undergo a relatively mild and benign clinical course, recent evidence suggested that COVID‐19 patients sustaining severe burn injuries may experience an amplified inflammatory response leading to delayed recovery and even serious debilitation. 14 , 30 Nevertheless, the common pathophysiological link between COVID‐19 and severe burn remains vastly unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the human coronavirus strain SARS‐CoV‐2 has thrown the world into the midst of a new pandemic, which remains an ongoing threat to human health. 29 Despite the fact that the majority of patients with SARS‐CoV‐2 infections undergo a relatively mild and benign clinical course, recent evidence suggested that COVID‐19 patients sustaining severe burn injuries may experience an amplified inflammatory response leading to delayed recovery and even serious debilitation. 14 , 30 Nevertheless, the common pathophysiological link between COVID‐19 and severe burn remains vastly unclear.…”
Section: Discussionmentioning
confidence: 99%